TRADITIONAL CONFLICT AND ITS INTERVENTIONS - Muhlis Muhlis (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
The Ngali-Renda conflict is habituated. It has taken for years. It has grown in its severity. It is not the case that the people of Ngali and Renda and the government do nothing in dealing with the conflict. However, the conflict is still there and waiting its trigger to appear. This research is significant in that it analyzes the traditional factors and interventions of the conflict. Applying qualitative research and historical, socio-cultural and phenomenological approaches showed that the Ngali-Renda conflict transformed from ndempa (empty-handed fighting) to lewa (armed fighting). Ndempa implied the spirit of honesty, openness and patriotism. It occurred every year in rest period of cultivation and took one or two month. Although ndempa was kapoda ade (serious and violent), it was kadihi ade (no intention to do harm) and for play and pleasure. On the contrary, lewa was more violent and caused casualties because the fighters used big knifes, arrows and firearms.